STRATEGI PENGEMBANGAN OBJEK WISATA LADUMA BERBASIS ENERGI TERBARUKAN SEBAGAI DAERAH TUJUAN WISATA (STUDI KASUS: SUBAK PINGE DESA BARU, KEC. MARGA, TABANAN) - Putu Fajar Kartika Lestari; Cening Kardi; Anak Agung Bagus Baskara (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
Ecotourism is a sub-component of the field of sustainable tourism. The potential of ecotourism which is considered an effective tool for sustainable development is the main reason why developing countries are now embracing it and incorporating it into economic development and conservation strategies. tourism potential in Indonesia that has a positive economic and cultural impact. Ecotourism development is very strategic because the approach used is alignment with the local community in order to be able to maintain local culture and at the same time improve their welfare. The purpose of this study is to determine internal and external factors in the development strategy of Laduma tourism objects in Taban Regency. This research was conducted on the tourist attraction Laduma. The respondents involved were 40 people, of which 15 people were taken from the party that manages the Salada tourist attraction, and as many as 25 people were tourists visiting the Laduma tourist attraction. Data collection using keusioner. Data analysis technique using SWOT Matrix. The results showed that the development of renewable energy- based laduma tourism objects as tourist destinations is in a strong position and has opportunities. The strategy recommendation given is aggressive, meaning that the Development of Laduma Tourism Objects Based on Renewable Energy as a Tourist Destination Area is in prime and steady condition so that it is possible to continue to develop optimally. Then the strategy recommendation given is the S-O strategy.